A Review on Membrane Technology and Chemical Surface Modification for the Oily Wastewater Treatment - Yalcinkaya, Fatma; Boyraz, Evren; Maryska, Jiri; Kucerova, Klara (Materials (Basel, Switzerland), 2020)
Cleaning of wastewater for the environment is an emerging issue for the living organism. The separation of oily wastewater, especially emulsified mixtures, is quite challenged due to a large amount of wastewater produced in daily life. In this review, the membrane technology for oily wastewater treatment is presented. In the first part, the global membrane market, the oil spill accidents and their results are discussed. In the second and third parts, the source of oily wastewater and conventional treatment methods are represented. Among all methods, membrane technology is considered the most efficient method in terms of high separation performance and easy to operation process. In the fourth part, we provide an overview of membrane technology, fouling problem, and how to improve the self-cleaning surface using functional groups for effectively treating oily wastewater. The recent development of surface-modified membranes for oily wastewater separation is investigated. It is believed that this review will promote understanding of membrane technology and the development of surface modification strategies for anti-fouling membranes.
Keywords: self-cleaning; surface modification; membrane; oil separation; nanomaterial